Infliximab-Induced Lupus: A Case Report - Pereira, Vítor Magno (2017)
We report the case of a 48-year-old, leukodermic female diagnosed with ulcerative proctitis for 4 years and latent tuberculosis. She was allergic to salicylates and had a minor allergic reaction to infliximab (rash, vertigo, and headache). Thereafter, she started azathioprine (2.5 mg/kg/day). She maintained intravenous infliximab, together with prophylaxis with clemastine and hydrocortisone, due to the steroid-dependent proctitis. The therapy was continued every 8 weeks with anti-tumor necrosis factor for about 3 years. The analytical evaluation when she was diagnosed with ulcerative proctitis (February 2011) showed negative antinuclear antibodies (ANA), double-stranded-DNA antibodies (anti-dsDNA), antineutrophil cytoplasmic antibodies and anti-Saccharomyces cerevisiae antibodies, and a positive outer membrane protein antibody. About 2 years and 6 months after starting infliximab (November 2013), the patient complained of inflammatory symmetrical polyarthralgia (knee, shoulder, elbow, and wrist) without synovitis, which started every week before the administration of infliximab. Resolution of symptoms was observed after each infliximab infusion. In July 2014, the autoantibody re-evaluation showed positive ANA with a homogeneous pattern with a titer of 1:640, weak positive anti-dsDNA (30.2), and positive anti-histone with C3 decreased (80.3). She was then diagnosed with lupus induced by infliximab and initiated hydroxychloroquine 400 mg. Infliximab was suspended. On re-evaluation, the erythrocyte sedimentation rate was 25 mm/h (1st hour), C-reactive protein 0.5 mg/dL (previously erythrocyte sedimentation rate 15 mm/h and C-reactive protein 1.2 mg/dL), and endoscopically, the mucosa was scarred, with some atrophy and scarce mucus in the lower rectum. About 10 months after discontinuation of infliximab, repeated autoantibodies proved all negative, keeping only low C3 (87). The patient also reported complete resolution of the arthralgia.